Natural Products in Cancer Prevention and Therapy - Pezzuto, John M.; Suh, Nanjoo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
G. D. Stoner L.-S. Wang Chemoprevention of Esophageal Squamous Cell Carcinoma with Berries C. S. Yang N. Suh Cancer Prevention by Different Forms of Tocopherols I. Almazari Y.-J. Surh Cancer Chemopreventive and Therapeutic Potential of Guggulsterone A. H. Conney Y.-R. Lou P. Nghiem J. J. Bernard G. C. Wagner Y.-P. Lu Inhibition of UVB-Induced Nonmelanoma Skin Cancer: A Path from Tea to Caffeine to Exercise to Decreased Tissue Fat C. Gerhauser Cancer Chemoprevention and Nutri-Epigenetics: State of the Art and Future Challenges Z.-Y. Su L. Shu T. O. Khor J. H. Lee F. Fuentes A.-N. T. Kong A Perspective on Dietary Phytochemicals and Cancer Chemoprevention: Oxidative Stress, Nrf2, and Epigenomics T. W. Kensler P. A. Egner A. S. Agyeman K. Visvanathan J. D. Groopman J.-G. Chen T.-Y. Chen J. W. Fahey P. Talalay Keap1-Nrf2 Signaling: A Target for Cancer Prevention by Sulforaphane A. T. Dinkova-Kostova Chemoprotection Against Cancer by Isothiocyanates: A Focus on the Animal Models and the Protective Mechanisms V. M. Adhami H. Mukhtar Human Cancer Chemoprevention: Hurdles and Challenges K. A. Gold E. S. Kim I. I. Wistuba W. K. Hong Personalizing Lung Cancer Prevention Through a Reverse Migration Strategy J. L. Wang K. A. Gold S. M. Lippman Natural-Agent Mechanisms and Early-Phase Clinical Development.
Chemoprevention of Esophageal Squamous Cell Carcinoma with Berries, by Gary D. Stoner and Li-Shu WangChemoprevention of Esophageal Squamous Cell Carcinoma with Berries, by Gary D. Stoner and Li-Shu Wang -- Cancer Prevention by Different Forms of Tocopherols, by Chung S. Yang and Nanjoo Suh -- Cancer Chemopreventive and Therapeutic Potential of Guggulsterone, by Inas Almazari and Young-Joon Surh -- Inhibition of UVB-Induced Nonmelanoma Skin Cancer: A Path from Tea to Caffeine to Exercise to Decreased Tissue Fat, by Allan H. Conney, You-Rong Lou, Paul Nghiem, Jamie J. Bernard, George C. Wagner and Yao-Ping Lu -- Cancer Chemoprevention and Nutri-Epigenetics: State of the Art and Future Challenges, by Clarissa Gerhauser -- A Perspective on Dietary Phytochemicals and Cancer Chemoprevention: Oxidative Stress, Nrf2, and Epigenomics, by Zheng-Yuan Su, Limin Shu, Tin Oo Khor, Jong Hun Lee, Francisco Fuentes and Ah-Ng Tony Kong -- Keap1-Nrf2 Signaling: A Target for Cancer Prevention by Sulforaphane, by Thomas W. Kensler, Patricia A. Egner, Abena S. Agyeman, Kala Visvanathan, John D. Groopman, Jian-Guo Chen, Tao-Yang Chen, Jed W. Fahey and Paul Talalay -- Chemoprotection Against Cancer by Isothiocyanates: A Focus on the Animal Models and the Protective Mechanisms, by Albena T. Dinkova-Kostova -- Human Cancer Chemoprevention: Hurdles and Challenges, by Vaqar Mustafa Adhami and Hasan Mukhtar -- Personalizing Lung Cancer Prevention Through a Reverse Migration Strategy, by Kathryn A. Gold, Edward S. Kim, Ignacio I. Wistuba and Waun K. Hong -- Natural-Agent Mechanisms and Early-Phase Clinical Development, by Janet L. Wang, Kathryn A. Gold and Scott M. Lippman.
Keywords: Chemistry; Cancer research; Molecular biology; Nutrition; Organic chemistry; Medical biochemistry; Biochemistry; Chemistry; Organic Chemistry; Cancer Research; Nutrition; Medical Biochemistry; Biochemistry, general; Molecular Medicine; Electronic books